Policy and strategies for quality improvement: a study on Chittagong City Corporation, Bangladesh - Quddus, S. M. Abdul (International Islamic University Malaysia, 2019)
The overall policy and strategies of an organization i.e. employee policy or employee development strategies, resource management as well as monitoring and control strategies characteristically have an effect on the quality management of the organization. These policies usually also have impact on the stakeholders i.e. satisfaction of the wider community and employees of the particular organization. The aim of this paper is to examine the policy and strategies of the Chittagong City Corporation for quality improvement and how these policy and strategies impact on the needs of its stakeholders. This paper is guided by the EFQM model as the theoretical underpinning that provides specific enabler criteria of quality management of organizations such as employee policy, development of partnerships and resource management, and the monitoring of strategies. These enabler criteria help to explain the ways in which total quality management (TQM) is implemented in any organization. Data for this study was collected from a total of 142 participants, including selective officials of the Chittagong City Corporation (CCC), city dwellers, government officials and civil society representatives by using a structured questionnaire. The findings of this study reveal that the CCC has failed to convey clearly its quality mission and objectives to its employees at all levels.